The changing face of my jazz photographic practice - Homer, Brian (Jazz Research Journal, 2024)
This article is a reflection on my jazz photography practice and how it has changed with my involvement in academic research after becoming actively involved in the Jazz Studies cluster at the Birmingham Centre for Media and Cultural Research (BCMCR), Birmingham City University and starting a close collaboration with jazz scholar Dr Pedro Cravinho. My practice evolved from photographing musicians playing at gigs to visualising the jazz scene and musicians from a different perspective which includes aspects of their off-stage lives. Through our discussions and common interests in the local jazz scene(s), Cravinho and I began developing a research process in which photography is the visual driver but is underpinned by Pedro’s rigorous academic input. Our collaboration is built on my documentary photography practice and Pedro’s ethnomusicological research background.